Analisis Pendidikan Karakter Pada Buku Teks Sejarah Kelas XI Kurikulum Merdeka - Pratiwi, Emilia; Sayono, Joko (Jayapangus Press, 2024)
This study is based on the discourse that Indonesia will experience a golden age in 2045 so it is necessary to prepare quality human resources so that it can provide positive things in accordance with what is expected. The education unit is the main gate of success. Not only creating quality human resources but education needs to shape character in accordance with national values to face challenges in the future. Based on this analysis, this study aims to describe the character education contained in the history textbook for class XI of the Merdeka Curriculum provided by the government as a learning facility. This study was conducted using content analysis with the history textbook grade XI Merdeka Curriculum as the subject and character education as the object. The existing data is then analyzed in a qualitative way by reducing data, presenting and drawing conclusions. From the study that has been carried out, a connecting line can be drawn that in the history textbook for class XI of the Merdeka Curriculum, which consists of four chapters starting from the colonialism period to the proclamation, there is character education in accordance with the indicators that have been formulated, which include spiritual, nationalist, independent, shoulder to shoulder, and integrity.